No Impact of Long-Term Fingolimod Treatment on Fecal Secretory Immunoglobulin A Levels in Patients With Multiple Sclerosis - Inojosa, Hernan; Eisele, Judith; Proschmann, Undine; Zeissig, Sebastian; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Cell and Developmental Biology, 2020)
Background. Fingolimod (FTY) is a sphingosine 1 phosphate (S1P) agonist with significant effects on immune cell distribution used as an effective disease modifying therapy in multiple sclerosis (MS) patients. Animal studies have demonstrated that a dysregulation of egress of murine secretory Immunglobulin A (sIgA)+ plasmablasts from Peyer’s patches in FTY-treated mice reduced fecal sIgA levels. Alterations in intestinal levels of sIgA could altermodify the gut microbiome and homeostasis in humans. We analyzed the effect of FTY on the fecal and salivary sIgA levels as marker of the humoral immune system in the gut. Methods. 25 people with confirmed MS diagnosis according to 2010 revised McDonald’s criteria and on long-term continuous treatment at the MS Center in Dresden, Germany were enrolled in this exploratory cross-sectional study. Fecal and salivary sIgA were analyzed after at least 12 months of treatment with FTY or Glatiramer acetate (GA). Results. 15 MS patients on FTY and 10 on GA participated in this study. The mean fecal sIgA concentration of both groups was not decreased compared to reference values and did not demonstrate significant differences between them (FTY 3356.96,6 µg/g +/- 2784.77; GA 2182.29 µg/g +/- 2255.3). A similar pattern was seen in the salivary sIgA and serum immunoglobulins levels. Conclusions: In this pilot study, we could not confirm the decrease of fecal sIgA after a long-term treatment with FTY. Further longitudinal studies should evaluate the effects of MS treatments on the gut immune system in more detail.